Participation in science and engineering laboratories for students with physical disabilities: survey development and psychometrics. - Jeannis, H.; Goldberg, M.; Seelman, K.; Schmeler, M.; Cooper, R. A. (Disability & Rehabilitation: Assistive Technology, 2019)
Purpose: The purpose of this study is to address the development of the Full Participation Science and Engineering Accessibility (FPSEA) self-report survey that gathers experiences from students with physical disabilities (SwD-P) using a postsecondary laboratory and to evaluate the survey's stability. Methods: Survey items were generated from an extensive literature review and recommendations articulated by experts. Think-aloud sessions and content validity index (CVI) were used to determine survey content validity and help finalize survey items. Individuals with physical disabilities (n = 20) who have taken a postsecondary science or engineering laboratory course completed the survey and took it again 10–14 days apart. The test–retest reliability was assessed using Spearman Rho coefficients for Likert-scale items, Chi-square and Fisher's exact test for the dichotomous items. Missing data completely at random (MCAR) test was computed before reliability data analysis. Results: Each sub-item passed the MCAR test, indicating that the data are missing completely at random and can be imputed to perform the analysis. Reliability analysis was completed on 20 individuals. The FPSEA had good content reliability: the item-level CVI of items kept ranged from 0.86 to 1. The scale-level CVI was 0.94. Stability was demonstrated with adequate Spearman correlation ranged from 0.56 to 0.86. Conclusions: No previous survey had been developed linking SwD-P and the postsecondary science and engineering (S&E) laboratory setting prior to this work. Overall, FPSEA is reliable and stable for reporting the barriers and facilitators to use S&E laboratories from the SwD-P's perspective. The barriers students with disabilities encounter in S&E laboratory environments are largely unknown. The FPSEA survey may help identify barriers and facilitators to using S&E laboratories for SwD-P. The FPSEA Survey allows former and current SwD-P to share their experiences using a postsecondary S&E instructional laboratory.